Retos en el modelado de la trazabilidad en las cadenas de suministro de alimentos - Maya, Tatiana; Orjuela Castro, Javier Arturo; Herrera, Milton Mauricio (Ingeniería, 2021)
Context: Changes in consumers’ eating interests have made the access to information related to specific products relevant, where food supply chain traceability (FSCT) has acquired a significant importance. Method: In order to identify the main issues and challenges in traceability systems and FSCT modeling, a systematic literature review was conducted, in which 84 articles were analyzed, and different taxonomies were presented for management, optimization, and simulation models. Then, a discussion was carried out about the challenges and future issues in FSCT modeling. Results: Limitations were identified in the types of decisions analyzed (tactical and operational), as well as an asymmetric flow of information between links, a lack of robust models, the relevance of information management as an integration tool, gaps in the measurement of technological management policies regarding traceability, the need for holistic models, and gaps in the relationship between traceability and sustainability. Conclusions: It is necessary to develop models based on technology management, as well as traceability systems that facilitate relations and flows between the different actors, the development of sustainable logistics management models involving traceability, the use of multi-criteria approaches relating multiple links, and quantifying different performance measurements in FSC to maximize the benefits of traceability by means of multi-objective models.